PENGARUH KEPEMIMPINAN, KEPUASAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION PADA KARYAWAN PERUSAHAAN PERS DALAM SMSI SULSEL - Syamsul Alam; Syamsul Ridjal; Abdul Samad; Muhammad Ashri Samad (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to determine the effect of leadership, job satisfaction and compensation on turnover intention in press company employees in the Indonesian Cyber ​​Media Union (SMSI) South Sulawesi (South Sulawesi). In collecting data, the writer uses the accidental sampling method with a sample of 32 respondents (employees). This research has been tested using a test instrument consisting of validity and reliability. In addition to the instrument test, the analysis used is the classical assumption test, hypothesis testing, and multiple linear regression testing using the SPSS 26.0 program. The results of the reseashowsshow that the first test is that leadership has a negative and insignificant effect on turnover intention, therefore leaders at press companies should change the leadership pattern that is in accordance with the character of the employees they have in order to build a good synergy to foster job satisfaction and comfort. The second test, job satisfaction has a negative and insignificant effect on turnover intention, this is a concern for the company that employees can survive not only because of job satisfaction but other things. Thus the third test, compensation has a negative and insignificant effect on turnover intention, the company's attention to compensation still needs seriousness and real implementation so that employees can stay longer at the company.